Spatial and seasonal variation of water quality parameters in surface water of Bued River - Mellizas, Marian Mae L.; Resurreccion, Augustus C.; Orozco, Christian R. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
River monitoring has proven to be an effective way to keep track of the water quality parameters. Seasonality in the hydrological processes in the area can help determine the behavior of these parameters in the river. Spatial variability on the other hand can help assess the role of point and non-point sources of pollution. In this study, spatial and seasonal variations of water quality parameters were observed in Bued River. Both historical and current data were analyzed for seasonal and spatial variability. Statistical techniques such as ANOVA, Pairwise comparison, T-test, Correlation Analysis, and PCA were used in order to determine the relationships and behavior of water quality parameters with respect to rainfall and spatial distribution. Results on historical and current data showed that water quality parameters were found to be at their maximum values during low rainfall events. Statistical analysis of spatial variation showed limited significant differences which suggest that water quality parameters were influenced by geologic factors rather than point sources. Comparison of current data with DAO 34 standards implies that Bued River is still fit for as a Class C river.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Water quality -- Measurement